Implementasi Metode Mind Mapping untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran Al-Qur'an Hadist di Kelas X MA ANNAZHAR - Khairil Anwar; Khairurrasyidi Khairurrasyidi (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the application of the Mind Mapping method in learning the Al-Qur'an Hadith in class X MA ANNAZHAR and measure its effectiveness in improving student understanding. This study uses a qualitative approach with a case study design that will be involved in in-depth interviews, participatory observations, and Focus Group Discussions (FGD). The results of the study indicate that the application of this method has a positive effect on a more systematic understanding of the relationship between Quranic poetry and hadith. Using branching diagrams allows students to better remember and understand the material, and feel more motivated and active in the learning process. Although there are several obstacles, such as time constraints and students' initial understanding of this technique, overall, the Mind Mapping method has proven effective in improving student understanding and learning outcomes. To optimize the application of this method, several suggestions are given, including training for teachers in teaching and demonstrating the effective use of concept maps, as well as more systematic time management in the curriculum. Initial provision is also needed for students so that they can use it with confidence. In addition, long-term evaluation is needed to assess the effectiveness of this method in maintaining students' understanding of the Al-Qur'an Hadith material, so that appropriate corrective steps can be taken to improve the quality of learning.